Proportion of foetal and placental implantation abnormalities in Madagascar: a cross-sectional study of 35,919 women at public-sector primary healthcare facilities in central and southern Madagascar, 2017-2020 - Krätzig, Franziska; Mei, Jie; Rebaliha, Mahery; Rampanjato, Zavaniarivo; Ranaivoson, Rinja; Razafinjato, Jenia; De Neve, Jan-Walter; Franke, Mara Anna; Muller, Nadine; Emmrich, Julius (PLOS ONE, 2024)
Background: Like other countries in sub-Saharan Africa, Madagascar has a high burden of maternal and neonatal mortality. However, as the proportion of foetal and placental abnormalities among the Malagasy population is unknown, strategies aimed at reducing maternal and neonatal mortality are challenging to define and implement. Methods: We conducted a multi-year, cross-sectional study using secondary NGO data on obstetric ultrasound, including patient records of all pregnant women who received an obstetric ultrasound screening between July 1st, 2017, and September 30th, 2020, at 62 public-sector primary care facilities in urban and rural regions of Madagascar. We analysed demographic characteristics and determined the prevalence of foetal and placental abnormalities. Results: The dataset included 38,688 ultrasound screening reports from 35,919 women, where 2,587/35,919 (7.20%) women had more than one ultrasound exam. Most women (68.63%, 26,550/38,688) received their first ultrasound during the third trimester of pregnancy. Foetal malpresentation at 36 weeks of gestation or later was diagnosed in 5.48% (176/3,211) of women with the breech presentation being most common (breech 3.99%, 128/3,211; transverse 0.84%, 27/3,211; mobile 0.5%, 16/3,211; oblique 0.16%, 5/3,211). Placenta previa was found in 2.31% (875/38,755) and multiple gestations in 1.03% (370/35,919) cases. Around one in every 150 women (0.66%, 234/38,702) had amniotic fluid disorders. Conclusion: The proportion of foetal and placental abnormalities detected by obstetric ultrasound is consistent with findings from other countries in sub-Saharan Africa. In contrast to current WHO recommendations, pregnant women, particularly those from rural, resource-constrained settings attend obstetric ultrasound screenings most commonly during their third trimester of pregnancy.
Gesehen am 02.10.2025